Tinjauan Yuridis Batas Usia Calon Wakil Presiden Dalam Putusan Mahkamah Konstitusi - Ni Putu Sintya Lestari; I Nyoman Suandika; Ida Bagus Anggapurana Pidada (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
The Constitutional Court's ruling on the age limit of a candidate vice president. With the results of research showing that, the regulation on a presidential candidate's age limit was less than 40 years later, it was only in the Act No. 7 of 2017 that the age limits of a vice president's candidate were 40 years. Since there are frequent changes in the age limit, it is necessary to clearly regulate the age of the candidate Vice President and harmonize the draft made by the House with the 1945 UUD to reduce the application for judicial review to the Constitutional Court.